2019
DOI: 10.1108/jbim-04-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Modelling SME e-commerce with IMAES

Abstract: Purpose There are several studies about the adoption of e-commerce for small-to-medium enterprises (SMEs) that separately, and in a dispersed manner, examine different theoretical approaches. The purpose of this paper is to unify a set of variables to form an integrated model of measurement of the adoption of e-commerce for SMEs. Design/methodology/discussion Based on an extensive review of empirical studies focused on the adoption of e-commerce in SMEs, a grouped and integrated model of e-commerce among SME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…The current study includes observability in the conceptual framework because social media use is highly observable, is transferable via WOM and recommendations from friends (Haridakis & Hanson, 2009) and can be stopped without additional cost (Valenzuela et al, 2009), so this factor may well be influential. The few studies that have examined the effect of observability on innovation adoption found mixed results, all indicating either a positive or a non-significant relationship (Chong and Pervan, 2007;Asare et al, 2016;Sanchez-Torres and Juarez-Acosta, 2019). In line with Rogers' model, it is expected that:…”
Section: H1 Social Media's Perceived Ease-of-use Will Positively Infmentioning
confidence: 99%
“…The current study includes observability in the conceptual framework because social media use is highly observable, is transferable via WOM and recommendations from friends (Haridakis & Hanson, 2009) and can be stopped without additional cost (Valenzuela et al, 2009), so this factor may well be influential. The few studies that have examined the effect of observability on innovation adoption found mixed results, all indicating either a positive or a non-significant relationship (Chong and Pervan, 2007;Asare et al, 2016;Sanchez-Torres and Juarez-Acosta, 2019). In line with Rogers' model, it is expected that:…”
Section: H1 Social Media's Perceived Ease-of-use Will Positively Infmentioning
confidence: 99%
“…In this study, we measure the use of e-commerce services in MSMEs to determine the e-commerce implementation process in MSME business processes, as well as the benefits that can be gained related to cost reduction, the speed and effectiveness of the marketplace performance process, improving communications, and other support. Therefore, the indicators used in this study, adopted from [23,87,89] are success of development, cost saving, communication improvement, marketplace performance, and overall satisfaction. -Supply chain performance: the supply chain consists of all parties involved-both directly and indirectly-in meeting customer demands [90].…”
Section: Operationalizing the Study Variablesmentioning
confidence: 99%
“…It describes the factors outside the firm that can affect its business such as competitors. Pressure from the competitors and customers or suppliers are valid examples of these environmental variables that influence the adoption of e-commerce in SMEs (Ahmad et al, 2014;Ghobakhloo et al, 2010;Sanchez-Torres & Juarez-Acosta, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%